The Determinants of Bank Default Risk: Evidence from the US Commercial Banks - Xiao, Xinyue (2019)
There are continuously increasing concerns about default risk since the global financial crisis. Banks dominate financial operations and are the most critical institutions in the financial system. It is particularly essential for commercial banks to manage risk, which is beneficial to the stability of the entire economic systems. This dissertation mainly focuses on the decisive factors of commercial bank default risk. This paper introduces the concept, measurement methods and influencing factors of default risk, and then it quantitatively examines the credit risks of 150 commercial banks in the United States from 2010 to 2018. The analysis consists of the macroeconomic factors and bank-level factors that influence on the default risks of commercial banks. On the basis of the existing literature, this paper selects six internal financial ratios and three external macroeconomic indicators as explanatory variables. It further establishes the panel data regression model to explore the relationship between the dependent variables and the independent variable Z-score. After analysing the empirical results, the macroeconomy is found to affect the US commercial bank default risk positively. From the perspective of individual level, cost-efficiency ratio and loan loss reserve ratio also influence on the default risk positively, while bank size affects the risk of default negatively.